Dynamic transcriptomic analysis of the early response of female flowers of Populus alba × P. glandulosa to pollination - Pian Rao (Nature Portfolio, 2017)
Abstract Pollination is an important event in plant sexual reproduction, and post-pollination response is an essential process for reproduction. Populus alba × P. glandulosa is used widely in scientific research, especially in cross breeding as parents. Adult female P. alba × P. glandulosa flowers are highly compatible with pollen from male P. tomentosa, but the early post-pollination response of flowers at the molecular levels is unclear. In this study, RNA-seq was employed to comprehensively understand the response of female P. alba × P. glandulosa flowers to pollination. Enrichment analysis reveals that the ‘plant hormone signal transduction’ pathway is enhanced during pollen-pistil interaction. Moreover, genes related to auxin, gibberellin and ethylene biosynthesis were significantly up-regulated. Ca2+ and H+-related genes and cell wall-related genes are interrelated, and all of them are essential for pollen tube elongation in pistil, especially, free Ca2+ providing a concentration gradient for pollen tube guidance and involved in signal transduction. Furthermore, RNA-seq results indicate that genes involved in the adhesion and guidance for pollen germination and pollen tube growth are abundantly present in the extracellular matrix. Our study provides an overview and detailed information for understanding the molecular mechanism of early post-pollination response in this hybrid poplar reproduction.